2017
DOI: 10.1159/000484245
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between RAS Association Domain Family Protein 1A Promoter Methylation and the Clinicopathological Characteristics in Patients with Ovarian Cancer: A Systematic Meta-Analysis

Abstract: Background: To investigate the relationship between RAS association domain family protein 1A (RASSF1A) promoter methylation and the clinical features, and the survival of ovarian cancer patients. Methods: A comprehensive literature search was conducted in the PubMed, Embase, EBSCO, and Cochrane Library databases. The overall ORs with their 95% CIs were calculated in this meta-analysis. Results: Finally 17 relevant publications with 1,108 ovarian cancer samples were available for the current meta-analysis. RASS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…However, most of this data has been obtained from cellular models or includes a limited number of samples. In contrast, RASSF1A promoter hypermethylation has been reported as an early event in several types of cancers, such as breast [ 34 ], ovarian [ 35 ], endometrial [ 36 ], and cervical [ 37 ], and has been related with prognostic, surveillance, and treatment response. To our knowledge, this is the first report on REST protein level in SIL/CIN and SCC tissue samples and cervical cancer cell lines.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, most of this data has been obtained from cellular models or includes a limited number of samples. In contrast, RASSF1A promoter hypermethylation has been reported as an early event in several types of cancers, such as breast [ 34 ], ovarian [ 35 ], endometrial [ 36 ], and cervical [ 37 ], and has been related with prognostic, surveillance, and treatment response. To our knowledge, this is the first report on REST protein level in SIL/CIN and SCC tissue samples and cervical cancer cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of the RE1 sequence in RASSF1A suggested a transcription repression mediated by REST. Previously, loss of RASSF1A expression has been reported in several types of cancer [ [34] , [35] , [36] , [37] ]; particularly in cervical cancer, in which a significant difference between non-SIL, LSIL, HSIL and SCC has been reported [ 40 ]. This has also been linked to cancer development, progression, metastasis, and poor prognosis [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…It plays an important role in the occurrence and development of esophageal cancer, which is consistent with the results of this group. It is suggested that RASSF1A is lowly expressed in esophageal squamous cell carcinoma tissues, which can accelerate the deterioration of cancer cells and promote the metastasis and invasion of cancer cells [29]. Kaplan–Meier single factor analysis showed that RASSF1A positive patients had higher survival time than negative patient.…”
Section: Discussionmentioning
confidence: 99%
“…RASSF1A promoter methylation has been reported to be markedly associated with EOC in a previous study on OC in Vietnamese women ( 64 ). However, a meta-analysis found that the levels of this modification were not substantially linked to the clinicopathological characteristics or the survival outcomes of patients with OC ( 65 ). This discrepancy may be due to differences in sample size or individual variations in experimental results.…”
Section: Tumor Suppressor Genesmentioning
confidence: 99%